Trajectories of alcohol use and consequences in college women with and without depressed mood. (February 2016) - Kenney, Shannon; Abar, Caitlin C.; O'Brien, Kimberly; Clark, Gabrielle; LaBrie, Joseph W.
Abstract: College students with depressed mood face heightened risk for experiencing drinking-related negative consequences. However, few studies have examined prospective patterns of alcohol consequences among depressed students. In the present investigation, we assessed how first-year college women's trajectories of heavy episodic drinking (HED) and alcohol consequences differed as a function of depressed mood at college entry. Participants were 233 heavy drinking incoming first-year college females (61% White) at a mid-sized West Coast University. Participants completed an online baseline survey, attended a single brief group intervention session, and completed 1- and 6-month post-intervention follow-up surveys. Depressed mood, alcohol consumption, and alcohol consequences were assessed at each time point. We employed latent growth curve analyses. Females with depressed mood, versus without depressed mood, experienced greater levels of alcohol consequences overall, particularly during transitions to college. However, contrary to hypotheses, participants with depressed mood (vs. without) exhibited significantly steeper declining trends in consequences, controlling for treatment condition, age, race, and ethnicity, and despite stable drinking levels, depressed mood, and use of protective behaviors over time. Potential explanations and suggestions for future research are discussed. Highlights: We examined women's trajectories of alcohol risk as a function of depressed mood. We examined alcohol-related trajectories during the first year of college. Depressed mood predicted increased alcohol risk during college, particular during college transitions. Depressed women exhibited steeper declines in consequences over time. Depressed women exhibited stable levels of mood, drinking and protective behaviors.